Strategi Kepala Sekolah dalam Mewujudkan Budaya Religius di SD Negeri Pandan Wangi 1 Malang - Sanjaka Yekti; Eka Danik Prahastiwi; Rudi Ruhardi (Pendidikan Agama Islam STIT Palapa Nusantara, 2022)
In an educational institution has a leader, namely the principal who is one of the keys to the success of the educational institution. To manage educational institutions with religious nuances, a professional strategy is needed managed by competent, responsible personnel, supported by infrastructure. This research is a field research using qualitative approach and descriptive data presentation. Data collection techniques are carried out with observation, interviews, and documentation. While the data analysis technique used is descriptive qualitative that is explorative. The results showed that: 1) The value of religious culture in SDN Pandanwangi 1 Malang is: a) Reading prayers and letters of the Qur'an before learning, b) Praying dhuha, dhuhur, and ashar in congregation, c) Commemoration of the islamic big day, d) and always dressed as Muslims. 2) The principal's strategy in realizing religious culture at SDN Pandanwangi 1 Malang is: a) Planning, b) Suri tauladan, b) Internalization of grades, c) Habituation, d) Evaluation. 3) The impact of religious cultural success at SDN Pandanwangi 1 Malang is it affects students, teachers, and schools. Changing the behavior habits of students to study such as reading prayers before learning, timely in praying, understanding the meaning of Islamic big day activities, and learning to wear clothes that are Muslim according to Islamic rules. In teachers and employees have an impact on changes in daily habit behavior, in providing a good example to students. And also make the image of the school better in the eyes of the community.